The impact of the Lesotho health reform in the re-structuring of the village health workers program - Afom T. Andom; Hannah N. Gilbert; Courtney M. Yuen; Mapoho Mokoroane; Melino Ndayizigiye; Mpopo Tsoele; Masebeo Koto; Retsepile Tlali; Makena Ratsiu; Joia S. Mukherjee (BMC Health Services Research)
Abstract Background Community Health Workers locally known as Village Health Workers (VHW) in Lesotho are key members of the primary health workforce, and has been playing a significant role in building primary health systems in many countries and they can fill significant gaps in human resources as low and middle income countries work towards universal health coverage in the era of Sustainable Development Goals (SDGs). The 2014 Lesotho health reform restructured the VHW program to compensate, professionalize, and integrate VHWs into primary care services. We sought to document the ways in which the VHW program changed as a result of the health reform and the perceived impact of those changes. Methods In 2018, we conducted a qualitative research study with an inductive content analysis approach in the four pilot health reform districts of Lesotho. We conducted 26 in-depth interviews with health workers practicing in the community and in primary health facilities, as well as district health authorities, and Ministry of Health officials. Results We found that the Lesotho health reform program was observed that it helped to professionalize the VHW program by introducing clear roles and responsibilities, regular monitoring, and supervision. The initiation of performance-based payment of VHWs and regular monitoring and reporting was thought contribute to overall improvement; in performance, strengthened links between communities and facilities, and promoted uptake of services. Conclusion The Lesotho Health Reform program was felt to be highly effective in re-structuring the VHW program in Lesotho, suggesting that when VHWs are well-incentivized, monitored, and supervised they can better fulfil their essential role as the backbone of the primary health workforce.